Novel small molecule inhibiting CDCP1‐PKCδ pathway reduces tumor metastasis and proliferation. Issue 5 (11th May 2017) - Nakashima, Katsuhiko; Uekita, Takamasa; Yano, Shigenobu; Kikuchi, Jun‐ichi; Nakanishi, Ruri; Sakamoto, Nozomi; Fukumoto, Keisuke; Nomoto, Akihiro; Kawamoto, Keisuke; Shibahara, Takashi; Yamaguchi, Hideki; Sakai, Ryuichi
Abstract : CUB domain‐containing protein‐1 (CDCP1) is a trans‐membrane protein predominantly expressed in various cancer cells and involved in tumor progression. CDCP1 is phosphorylated at tyrosine residues in the intracellular domain by Src family kinases and recruits PKCδ to the plasma membrane through tyrosine phosphorylation‐dependent association with the C2 domain of PKCδ, which in turn induces a survival signal in an anchorage‐independent condition. In this study, we used our cell‐free screening system to identify a small compound, glycoconjugated palladium complex (Pd‐Oqn), which significantly inhibited the interaction between the C2 domain of PKCδ and phosphorylated CDCP1. Immunoprecipitation assays demonstrated that Pd‐Oqn hindered the intercellular interaction of phosphorylated CDCP1 with PKCδ and also suppressed the phosphorylation of PKCδ but not that of ERK or AKT. In addition, Pd‐Oqn inhibited the colony formation of gastric adenocarcinoma 44As3 cells in soft agar as well as their invasion. In mouse models, Pd‐Oqn markedly reduced the peritoneal dissemination of gastric adenocarcinoma cells and the tumor growth of pancreatic cancer orthotopic xenografts. These results suggest that the novel compound Pd‐Oqn reduces tumor metastasis and growth by inhibiting the association between CDCP1 and PKCδ, thus potentially representing a promising candidate among therapeutic reagents targeting protein–protein interaction. Abstract : CDCP1 is involved in tumor metastasis through forming complex with PKCdelta. We discovered Pd‐Oqn, a small molecule, that disrupts the interaction of CDCP1 with PKCdelta by chemical screening. Pd‐Oqn attenuated anchorage‐independent growth of tumor cells and metastasis in mouse model.